Relationships between minimum alcohol pricing and crime during the partial privatization of a Canadian government alcohol monopoly - Stockwell, Tim; Zhao, J.; Marzell, M.; Gruenewald, P.; Macdonald, S.; Ponicki, W.; Martin, G. (Alcohol Research Documentation Inc., 2015)
Objective: The purpose of this study was to estimate the independent effects of increases in minimum alcohol prices and densities of private liquor stores on crime outcomes in British Columbia, Canada, during a partial privatization of off-premise liquor sales. Method: A time-series cross-sectional panel study was conducted using mixed model regression analysis to explore associations between minimum alcohol prices, densities of liquor outlets, and crime outcomes across 89 local health areas of British Columbia between 2002 and 2010. Archival data on minimum alcohol prices, per capita alcohol outlet densities, and ecological demographic characteristics were related to measures of crimes against persons, alcohol-related traffic violations, and non–alcohol- related traffic violations. Analyses were adjusted for temporal and regional autocorrelation. Results: A 10% increase in provincial minimum alcohol prices was associated with an 18.81% (95% CI: ±17.99%, p < .05) reduction in alcohol-related traffic violations, a 9.17% (95% CI: ±5.95%, p < .01) reduction in crimes against persons, and a 9.39% (95% CI: ±3.80%, p < .001) reduction in total rates of crime outcomes examined. There was no significant association between minimum alcohol prices and non–alcohol-related traffic violations (p < .05). Densities of private liquor stores were not significantly associated with alcohol involved traffic violations or crimes against persons, though they were with non–alcohol-related traffic violations. Conclusions: Reductions in crime events associated with minimum-alcohol-price changes were more substantial and specific to alcohol-related events than the countervailing increases in densities of private liquor stores. The findings lend further support to the application of minimum alcohol prices for public health and safety objectives.